2021
DOI: 10.1111/ecc.13400
|View full text |Cite
|
Sign up to set email alerts
|

Rapid screener for the assessment of fear of progression in cancer survivors: The Fear of progression‐Questionnaire Rapid Screener

Abstract: Fear of Progression (FoP) describes the fear that the cancer will progress or return (Dinkel & Herschbach, 2018) and is included in the international definition of fear of cancer recurrence (FCR) (Lebel et al., 2016). Even though FoP can be seen as a normal and adaptive response to a real threat, it can reach clinically relevant levels that considerably impair all areas of daily life (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Scores of 34 or above indicate dysfunctional levels of FoP [33,34]. Recently, a 5-item short-form version of the FoP-Q-12 has been developed [30], called FoP-Q-RS. Here, we prefer the notation FoP-Q-5.…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scores of 34 or above indicate dysfunctional levels of FoP [33,34]. Recently, a 5-item short-form version of the FoP-Q-12 has been developed [30], called FoP-Q-RS. Here, we prefer the notation FoP-Q-5.…”
Section: Instrumentsmentioning
confidence: 99%
“…A frequently used and validated instrument for assessing FoP in cancer patients is a short form of the FoP-Q, the FoP-Q-12 [29]. A recent study further condensed this questionnaire and extracted five items, arriving at the 5-item Fear of Progression Questionnaire-Rapid Screener (FoP-Q-RS) [30]. Another recently developed short questionnaire for measuring FoP is the Concerns About Recurrence Questionnaire CARQ-4 [31].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that 33 to 96% of cancer patients worldwide have FoP, and the proportion with severe fear reaches 87% (Lebel et al, 2016). FoP has become one of the most common psychological problems in patients with cancer, and FoP is now included in the international definition of fear of cancer recurrence (FCR; Youssef et al, 2021). FCR is fear or apprehension in cancer survivors about the possibility of cancer recurrence, progression, or metastasis at the primary site or elsewhere (Barrows et al, 2020).…”
Section: Introductionmentioning
confidence: 99%